How to explain and fight organizational crime - Pohlmann, Markus; Mitra, Subrata Kumar; Dannecker, Gerhard; Dölling, Dieter; Hermann, Dieter; Höly, Kristina; Trombini, Maria Eugenia (Organizational crime, 2023)
Why does non-compliance, caused by organizational crime, persist, not only in countries reputed to be high on the global list for corruption but also in Western countries that are considered to be relatively non-corrupt? The book investigates this problem in a comparative framework, with samples from both developed economies with long traditions of regulatory frameworks and emerging economies which are relatively new to the culture and framework of regulation. The contributors to this book have investigated this phenomenon in many areas of the global political economy, corporate culture, and behavior, both in the areas of industry as well as the health sector. The book concludes that the mechanical imposition of global regulatory norms on countries where such rules of behavior are not yet a part of the culture and the collective mindset is likely to be less than effective, producing mere “window dressing” rather than effective compliance. The global diffusion of regulatory norms and the creation of a global culture of regulation and self-regulation is a complex and interactive process that entails patience and careful monitoring.
Gesehen am 10.05.2023